(untitled) (Research, Society and Development, 2020)
This study aimed to learn about the preparation and training of professionals in the Family Health Strategy to work in the detection and intervention of Postpartum Maternal Depression, based on an exploratory descriptive study carried out in four Basic Family Health Units, from June to September 2016, through semi-structured interviews, analyzed by means of Thematic Content Analysis. The results of the data analysis were compiled into two thematic categories: The unpreparedness of health professionals in the face of Postpartum Depression and The recognition of the need for training on Postpartum Depression. Despite the unpreparedness and lack of technical and scientific training of health professionals to identify and intervene in maternal postpartum depression, workers recognized the need for educational actions to qualify the assistance provided by them. Thus, it is understood that the National Policy for Permanent Education in Health must be effectively incorporated into Primary Care services, as well as permanent education actions must be implemented and maintained in the work routine of the Family Health Strategy, addressing themes diversified, especially those in which the team finds weaknesses, such as postpartum depression. It is also worth mentioning the need for interprofessional efforts, to ensure adequate preparation of workers and qualification of assistance to women in their puerperal pregnancy cycle, with examples such as psychological prenatal care and matrix support.